CHILDREN WITH SPECIAL NEEDS IN THE DENTAL OFFICE - Jeremic, Marko; Vukovic, Ana; Markovic, Dejan; Ciric, Predrag (HEALTH CARE, 2020)
People with disabilities may experience negative relation between their own personal potentials compared to environmental expectations and potentials of healthy peers in terms of functional participation and activity limitations. Therefore, they usually need an individualized dental treatment plan. Dentists have an important role in maintaining and improving oral health in this vulnerable group. Having in mind the United Nation’s Declaration on Human Rights, patients with disabilities have human rights to achieve equal health outcomes as their healthy peers. Therefore, all preventive, prophylactic, and therapeutic interventions need to be carefully planned. In addition to precise medical history, the dentist should also have basic psychological knowledge to adjust the approach to patient’s needs. Improving the oral health of patients with disabilities involves a primary, secondary, or tertiary level of oral health care, depending on patient’s abilities and needs. The team work and a multidisciplinary approach, with the cooperation of experts of different profiles and specialties, is the only approach that gives satisfactory results.